Semantic web collaborative spaces : second International Workshop, SWCS 2013, Montpellier, France, May 27, 2013, third International Workshop, SWCS 2014, Trentino, Italy, October 19, 2014, Revised selected and invited papers /: second International Workshop, SWCS 2013, Montpellier, France, May 27, 2013, third International Workshop, SWCS 2014, Trentino, Italy, October 19, 2014, Revised selected and invited papers. (2016) - Unknown
No abstract available